Wage Floor Rigidity in Industry-Level Agreements: Evidence from France - Denis Fougère; Erwan Gautier; Sébastien Roux (Institute of Labor Economics (IZA), 2018)
This paper examines empirically the dynamics of wage floors defined in industry-level wage agreements in France. It also investigates how industry-level wage floor adjustment interacts with changes in the national minimum wage (NMW hereafter). For this, we have collected a unique dataset of approximately 3,200 industry-level wage agreements containing about 70,000 occupation-specific wage floors in 367 industries over the period 2006Q1-2017Q4. Our main results are the following. Wage floors are quite rigid, adjusting only once a year on average. They mostly adjust in the first quarter of the year and the NMW shapes the timing of industry-level wage bargaining. Inflation but also changes in past aggregate wage increases and in the real NMW are the main drivers of wage floor adjustments. Elasticities of wage floors with respect to these macro variables are 0.6, 0.4 and 0.3 respectively. Inflation and the NMW have both decreasing but positive effects all along the wage floor distribution.
Keywords: J31; J51; E24; 330; collective bargaining; wages; minimum wage; inflation